Winter tourism in Portugal - encouraging its increase - Garcia, Raul Ressano (2014)
Every year between seventy thousand and one hundred thousand Portuguese practice winter sports,mainly skiing and snowboarding (Carvalho, 2006). Unfortunately for Portuguese tourism most of them go abroad to spend their money.Serra da Estrela is the only mountain where it is possible to practice winter sports in Portugal but it doesn’t attract many Portuguese. Problems with accessibility (Petur,2006) inexistency of accommodation near the ski slopes (Carvalho,2006) and not enough kilometers of ski slopes(Tonge, Veronica) are some of the main reasons for this lack of attraction.The aim of this paper is to demonstrate that is possible to increment the number of kilometers of ski slopes in Serra da Estrela.To provide the design of the new ski slopes we went to the mountain and marked over a thousand points in GPS. These points marked on the field provide us the information to design the new ski slopes. These new ski slopes will help Serra da Estrela to become more attractive, avoiding the need for Portuguese to go abroad to practice winter sports.